The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1007/s00705-007-0944-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of ecologically distinct Mal de Río Cuarto virus isolates based on restriction fragment length polymorphism (RFLPs) and genome sequence analysis of segments 1, 7, 9 and 10

Abstract: Viruses of the species Mal de Río Cuarto virus (genus Fijivirus, family Reoviridae) cause significant economic losses in maize in Argentina. Genetic changes in the virus genome leading to better adaptation to diverse ecological conditions were postulated that would account for the increasing MRCV variability. The genomic differences between MRCV isolates from four ecologically different areas (Río Cuarto, RC; Pergamino, P; Jesús María, JM; and Tafí del Valle, TV) were studied. RT-PCR-amplified fragments compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…2003). Four MRCV isolates from different regions in Argentina shared over 96% nucleotide identity (Giménez‐Pecci et al. 2007), and 25 FDV isolates from Australia, Papua New Guinea and Malaysia had more than 85% nucleotide identity (Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2003). Four MRCV isolates from different regions in Argentina shared over 96% nucleotide identity (Giménez‐Pecci et al. 2007), and 25 FDV isolates from Australia, Papua New Guinea and Malaysia had more than 85% nucleotide identity (Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sequences of rice and maize RBSDV isolates from different geographical regions show more than 90% nucleotide identity (Zhang et al 2001a,b;Wang et al 2003). Four MRCV isolates from different regions in Argentina shared over 96% nucleotide identity (Gime´nez-Pecci et al 2007), and 25 FDV isolates from Australia, Papua New Guinea and Malaysia had more than 85% nucleotide identity (Jiang et al 2008). In addition, we recently sequenced the partial outer capsid protein gene of more than 100 SRBSDV isolates from different areas in China and Vietnam and found that the sequences were over 97% nucleotide identical (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…dsRNA , GenBank RBSDV , S9 S10 90%( 4 7); , Giménez-Pecci [22] 4 MRCV S1, S7, S9 S10 , 96%; Jiang [23] 25 FDV…”
Section: Srbsdv S10unclassified